Pengaruh Praktek Kerja Industri (Prakerin) dan Mata Pelajaran Produktif terhadap Minat Berwirausaha melalui Self efficacy pada Siswa Jurusan Bisnis Daring dan Pemasaran SMK N 1 Jombang - Niko Husna Satria; Finisica Dwijayanti Patrikha (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
Research aims to determine the effect of industrial work practices (prakerin) and productive subjects on entrepreneurial interest through the Self-Efficacy of students majoring in Online Business and Marketing at SMKN 1 Jombang. The sample in this study was 103 students. The results of the research describe that partially 1) No influence of industrial work practices (prakerin) on entrepreneurial interest, 2) Positive and significant influence on productive subjects on entrepreneurial interest, 3) Positive and significant influence on Self-Efficacy on entrepreneurial interest, 4) Finding a positive and significant influence on industrial work practices (prakerin) on Self-Efficacy, 5) Not finding the effect of productive subjects on Self-Efficacy, 6) Finding a positive and significant influence on industrial work practices on interest in entrepreneurship through Self-Efficacy as a moderating variable, 7) Found positive and significant effect of productive subjects on interest in entrepreneurship through Self-Efficacy as a moderating variable.